Antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis in chronic Hepatitis B: Unraveling the immune puzzle - a rare case report with review of literature - Suresh Bhagoowani; Uooja Devi; Aqsa Munir; Ummulkiram Hasnain; Javed Iqbal (IDCases)
Background: Hepatitis B virus (HBV) infection affects millions worldwide, predominantly targeting the liver, leading to conditions like cirrhosis and hepatocellular cancer. However, HBV can also cause extrahepatic complications, including autoimmune-mediated vasculitis. Small vessel vasculitis, often associated with antineutrophil cytoplasmic antibodies (ANCA), can occur in chronic infections like HBV. Case presentation: A 46-year-old man with chronic hepatitis B presented with high fever, diarrhoea, and painful black discolouration on his nose, fingers, and toes. Lab results revealed anaemia, leukocytosis, elevated inflammatory markers, positive c-ANCA, and HBV PCR positivity. He was diagnosed with c-ANCA-associated small vessel vasculitis secondary to chronic hepatitis B. Treatment with methylprednisolone followed by tapering prednisolone and azathioprine led to significant improvement in his condition. Conclusion: This case highlights the rare occurrence of c-ANCA-associated vasculitis in chronic HBV without typical liver symptoms. ANCA testing may aid in early diagnosis and management of such cases. Further research is needed to explore the underlying immunological mechanisms and refine therapeutic approaches.